An Unusual Etiology of Fluorodeoxyglucose Avid Intrathoracic Lymph Nodes - Bonnier, Alyssa; Saha, Santu; Austin, Adam; Saha, Biplab K (Prague medical report, 2024)
A middle-aged man in his 50s, active smoker, presented to the pulmonary office for lung cancer evaluation. On a low-dose computed tomography for lung cancer screening, he was found to have an 8 mm endobronchial lesion in the right main stem bronchus. A PET-CT revealed no endobronchial lesion, but incidentally, fluorodeoxyglucose (FDG) avidity was present in the right hilar (SUV 13.2) and paratracheal lymph nodes (LNs). He underwent bronchoscopy and EBUS-TBNA of station 7 and 10 R LNs. The fine needle aspiration (FNA) revealed necrotizing epithelioid granuloma. The acid-fast bacilli (AFB) and Grocott methenamine silver (GMS) stains were negative. He had suffered from pneumonic tularemia 13 months ago and immunohistochemical staining for Francisella tularensis on FNA samples at Center for Disease Control and Prevention was negative. The intense positron emission tomography (PET) avidity was attributed to prior tularemic intrathoracic lymphadenitis without active tularemia, a rare occurrence. To the best of our knowledge, PET-positive intrathoracic lymph node beyond one year without evidence of active tularemia has not been previously reported.
Keywords: Pneumonia; PET-CT; časná detekce nádoru; Positron Emission Tomography Computed Tomography; nádory plic; tularemie; fluorodeoxyglukosa F18; lymfatické uzliny; lidé; Lymph nodes; PET/CT; staging nádorů; Tularemia; Endoscopic Ultrasound-Guided Fine Needle Aspiration; retrospektivní studie; biopsie tenkou jehlou pod endosonografickou kontrolou; Male; Lymph Nodes; Lung Neoplasms; Early Detection of Cancer; lidé středního věku; Fluorodeoxyglucose F18; mužské pohlaví; Retrospective Studies; Middle Aged; Neoplasm Staging; Humans